Evaluation of neurological effects of cerium dioxide nanoparticles doped with different amounts of zirconium following inhalation exposure in mouse models of Alzheimer's and vascular disease. (September 2020) - Wahle, Tina; Sofranko, Adriana; Dekkers, Susan; Miller, Mark R.; Heusinkveld, Harm J.; Albrecht, Catrin; Cassee, Flemming R.; Schins, Roel P.F.
Abstract: Increasing evidence from toxicological and epidemiological studies indicates that the brain is an important target for ambient (ultrafine) particles. Disturbance of redox-homeostasis and inflammation in the brain are proposed as possible mechanisms that can contribute to neurotoxic and neurodegenerative effects. Whether and how engineered nanoparticles (NPs) may cause neurotoxicity and promote neurodegenerative diseases such as Alzheimer's disease (AD) is largely unstudied. We have assessed the neurological effects of subacute inhalation exposures (4 mg/m 3 for 3 h/day, 5 days/week for 4 weeks) to cerium dioxide (CeO2 ) NPs doped with different amounts of zirconium (Zr, 0%, 27% and 78%), to address the influence of particle redox-activity in the 5xFAD transgenic mouse model of AD. Four weeks post-exposure, effects on behaviour were evaluated and brain tissues were analysed for amyloid-β plaque formation and reactive microglia (Iba-1 staining). Behaviour was also evaluated in concurrently exposed non-transgenic C57BL/6J littermates, as well as in Western diet-fed apolipoprotein E-deficient (ApoE -/- ) mice as a model of vascular disease. Markers of inflammation and oxidative stress were evaluated in brain cortex. The brains of the NP-exposed 5xFAD mice revealed no accelerated amyloid-β plaque formation. No significant treatment-related behaviour impairments were observed in the healthy C57BL/6J mice. In the 5xFAD and ApoE -/- models, the NP inhalation exposures did not affect the alternation score in the X-maze indicating absence of spatial working memory deficits. However, following inhalation exposure to the 78% Zr-doped CeO2 NPs changes in forced motor performance (string suspension) and exploratory motor activity (X-maze) were observed in ApoE -/- and 5xFAD mice, respectively. Exposure to the 78% doped NPs also caused increased cortical expression of glial fibrillary acidic protein (GFAP) in the C57BL/6J mice. No significant treatment-related changes neuroinflammation and oxidative stress were observed in the 5xFAD and ApoE -/- mice. Our study findings reveal that subacute inhalation exposure to CeO2 NPs does not accelerate the AD-like phenotype of the 5xFAD model. Further investigation is warranted to unravel whether the redox-activity dependent effects on motor activity as observed in the mouse models of AD and vascular disease result from specific neurotoxic effects of these NPs. Highlights: 4-week mouse inhalation study with 0%, 27% and 78% Zr-doped CeO2 nanoparticles. No acceleration of Alzheimer-related features in 5xFAD mouse model. Motor performance changes in 78% Zr-doped CeO2 exposed ApoE -/- and 5xFAD mice. Increased GFAP levels in 78% Zr-doped CeO2 exposed C57BL/6J mice.